A high-entropy phosphate catalyst for oxygen evolution reaction. (August 2021) - Qiao, Haiyu; Wang, Xizheng; Dong, Qi; Zheng, Hongkui; Chen, Gang; Hong, Min; Yang, Chun-Peng; Wu, Meiling; He, Kai; Hu, Liangbing
Abstract: Transition metal phosphates are a class of catalysts that are widely used in biologic reactions, organic synthesis, oxygen evolution, and photocatalysis. While previous studies have shown the catalytic performance can be greatly benefited from incorporating multiple elements, high-entropy polyanionic materials such as high-entropy phosphates (HEPi) have never been reported due to the harsh synthetic requirement of a short high-temperature heating duration. Herein we for the first time report the synthesis of HEPi catalyst ( i.e., CoFeNiMnMoPi) in the form of highly uniform spherical particles through a high-temperature fly-through method. Our approach enables (1) uniformly confined metal and phosphorous precursors in one aerosol droplet, (2) in-situ oxide-to-phosphate transformation at high temperature, and (3) homogenous mixing of multi-metallic elements in a phosphate structure in milliseconds. As a proof-of-concept, we apply the HEPi catalyst in a model oxygen evolution reaction (OER), where much lower overpotential (270 mV at 10 mA cm −2 ) and faster kinetics (Tafel slope of 74 mV dec −1 ) were measured compared to the commercial IrOx and the high-entropy oxide (HEO) counterpart. This study paves a new way toward synthesizing a library of high-entropy polyanionic compounds for a range of applications in energy and catalysis. Graphical Abstract: ga1 Highlights: A high-entropy phosphate catalyst is synthesized for the first time. A transient high-temperature heating leads to in situ oxide-to-phosphate transformation. The catalyst exhibits superior performance in oxygen evolution reaction.